Research status & challenges on prevention and control technology for thermal runaway combustion-explosion of lithium-ion battery in coal mines - Yongzheng YAO; Yiyuan WANG; Fubao ZHOU (Meitan xuebao)
With the continuous promotion of the “carbon neutral& carbon peak” process, the energy electronics industry that deeply integrates lithium-ion energy storage batteries, information technology and coal mines is flourishing. A new industry for the application of lithium-ion batteries in coal mines has emerged. In the first four natural months of 2024, MA certification for “lithium” increased by 94% year-on-year. While the new industry has brought development opportunities for the green transformation of coal mines, new risks have also arisen. As a high-energy object, lithium-ion batteries still inherently carry the risk of fire or explosion. Once the battery experiences thermal runaway in in the confined space of coal mines, the consequences of the disaster are unimaginable. Besides, to ensure the safe of lithium-ion batteries in coal mines, the batteries are placed inside explosion-proof housings made of high-strength steel plates of 1−2 cm thick with plenty of redundant space, which limits the endurance of the equipment and the process of applying lithium-ion batteries to large-scale auxiliary transport and mining equipment. In order to reduce the risk of thermal runaway of lithium-ion batteries in coal mines, improve equipment endurance, and promote the development of lithium-ion batteries in coal mines in depth, this study focus on the safety problem of large capacity lithium-ion batteries in coal mines, analyzing the research status and shortcomings in six aspects: thermal runaway mechanism, safety evaluation and management, monitoring and early warning, power structure and function design, charging and swapping safety and emergency response. Besides, six key issues that urgently need to be addressed in coal mines for the safety of lithium-ion batteries are proposed, including the coupled disaster triggering mechanism between lithium-ion battery combustion and explosion and common coal mine disasters in typical scenarios, the development of high safety lithium-ion batteries in coal mines, the thermal runaway advanced warning technology and monitoring strategy of lithium-ion battery, the high strength, flame retardant, explosion-proof and lightweight design of lithium-ion power, the intelligent and safe of charging & switching technology and equipment, and rapid control technology for thermal runaway explosion disasters. These are expected to provide guidelines for solving the safety problem and insufficient endurance problem of lithium-ion batteries in the new industry.